VD_FINDINFO HC / 2012 / 37 vom 18. Januar 2012 - VD Tribunal cantonal (2012)
JONCTION DE CAUSES, DOMMAGE IRRÉPARABLE | 124 al. 1 CPC (CH), 125 let. b CPC (CH), 125 let. c CPC (CH), 319 let. b ch. 2 CPC (CH), 322 al. 1 CPC (CH)